Land Rental Markets in the Process of Rural Structural Transformation: Productivity and Equity Impacts from China - Jin, Songqing; Deininger, Klaus (2012)
Although the importance of land rental for overall economic development and development of the non-agricultural economy has long been recognized in theory, empirical evidence on factors that can promote or impede operation of such markets and their productivity and equity impacts, especially in rapidly developing economies with rather equal land endowments, remains limited. A large household level panel is used to illustrate the large contribution of land markets to occupational diversification, productivity of land use, and household welfare. Factors affecting land market participation are derived from a household model with transaction cost and individual ability. Results suggest that, by transferring land from less able and more affluent households who joined the non-farm sector to poorer ones with ample family labor, land markets are critical not only for non-agricultural growth but, by allowing more effective use of potentially idle land can contribute to significant productivity gains. Policy implications are derived.